Kinanthropometry VIII : proceedings of the 8th International Conference of the International Society for the Advancement of Kinanthropometry (ISAK) /: proceedings of the 8th International Conference of the International Society for the Advancement of Kinanthropometry (ISAK). (2005) - Unknown
No abstract available